2012
DOI: 10.1007/s11427-012-4292-0
|View full text |Cite
|
Sign up to set email alerts
|

Sulfolobus tokodaii RadA paralog, stRadC2, is involved in DNA recombination via interaction with RadA and Hjc

Abstract: Rad51/RadA paralogs found in eukaryotes and euryarchaea play important roles during recombination and repair, and mutations in one of the human Rad51 paralogs, Rad51C, are associated with breast and ovarian cancers. The hyperthermophilic crenarchaeon Sulfolobus tokodaii encodes four putative RadA paralogs and studies on these proteins may assist in understanding the functions of human Rad51 paralogs. Here, we report the biochemical characterization of stRadC2, a S. tokodaii RadA paralog. Pull-down assays revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Mre11-Rad50 initiates DNA end resection and degrades 5′ ssDNA in concert with HerA-NurA (Hopkins and Paull, 2008; Quaiser et al, 2008; Zhang et al, 2008; Blackwood et al, 2012; Rzechorzek et al, 2014). The resulting 3′ ssDNA is bound by RadA and strand invasion was performed with the help of several RadA paralogues, Rad54, RadC1 and RadC2 (Haseltine and Kowalczykowski, 2009; McRobbie et al, 2009; Liang et al, 2013; Wang et al, 2013). The SF-II helicase Hjm and PINA, a recently identified ATPase, are supposed to be responsible for HJ migration (Li et al, 2008; Woodman and Bolt, 2009; Song et al, 2016; Zhai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mre11-Rad50 initiates DNA end resection and degrades 5′ ssDNA in concert with HerA-NurA (Hopkins and Paull, 2008; Quaiser et al, 2008; Zhang et al, 2008; Blackwood et al, 2012; Rzechorzek et al, 2014). The resulting 3′ ssDNA is bound by RadA and strand invasion was performed with the help of several RadA paralogues, Rad54, RadC1 and RadC2 (Haseltine and Kowalczykowski, 2009; McRobbie et al, 2009; Liang et al, 2013; Wang et al, 2013). The SF-II helicase Hjm and PINA, a recently identified ATPase, are supposed to be responsible for HJ migration (Li et al, 2008; Woodman and Bolt, 2009; Song et al, 2016; Zhai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similar proteins (KaiC) are found in some bacteria, likely from horizontal gene transfer (Leipe et al 2000;Haldenby et al 2009). Limited biochemical (Sheng et al 2008;McRobbie et al 2009;Wang et al 2012;) and genetic (Liang et al 2013) data available suggests that aRadC proteins are involved DNA repair by HR. aRadC group members bind to ssDNA (Sheng et al 2008;McRobbie et al 2009;Wang et al 2012;.…”
Section: Mediators Of Dna-strand-exchange Proteinsmentioning
confidence: 99%
“…Limited biochemical (Sheng et al 2008;McRobbie et al 2009;Wang et al 2012;) and genetic (Liang et al 2013) data available suggests that aRadC proteins are involved DNA repair by HR. aRadC group members bind to ssDNA (Sheng et al 2008;McRobbie et al 2009;Wang et al 2012;. A stimulatory or inhibitory effect of aRadC on RadA activities (strand-exchange assays, ssDNA binding, or ATPase activity) was detected in all biochemical studies in which it was analyzed (Sheng et al 2008;McRobbie et al 2009;Wang et al 2012;, and one study reported release of the SSB inhibitory effect in a strand-exchange assay suggesting a mediator function (Sheng et al 2008).…”
Section: Mediators Of Dna-strand-exchange Proteinsmentioning
confidence: 99%
“…Characterization of RadC proteins of Sulfolobus has yielded some insight into their possible functions. Biochemical studies showed that one of RadC members in S. tokodaii , RadC1 (Sto0579), enhances the ATPase and strand invasion activities of RadA [79], while another RadC member, RadC2 (Sto1830), interacts with both RadA and Hjc, a Holliday junction resolvase [80]. In vivo functional analyses have shown that two archaeal homologs, RadC1 and RadC2, in S. islandicus are involved in DNA repair [81], though the exact role of RadC1 in HR is still under debate [66,79,82].…”
Section: Other Archaeal Aaa + Atpases Involved In Dna Repairmentioning
confidence: 99%